Distinct Bleaching Resilience of Photosynthetic Plastid-Bearing Mollusks Under Thermal Stress and High CO2 Conditions - Dionísio, Gisela; Faleiro, Filipa; Bispo, Regina; Lopes, Ana Rita; Cruz, Sónia; Paula, José Ricardo; Repolho, Tiago; Calado, Ricardo; Rosa, Rui (Frontiers in Physiology, 2018)
The impact of temperature on photo-symbiotic relationships has been highly studied in the tropical reef-forming corals but overlooked in less charismatic groups such as solar-powered sacoglossan sea slugs. These organisms display one of the most puzzling symbiotic features observed in the animal kingdom, i.e. their mollusk-plastid association, which enables them to retain photosynthetic active chloroplasts (i.e. kleptoplasts) retrieved from their algae feed sources. Here we analyse the impact of thermal stress (+4ºC) and high pCO2 conditions (∆pH=0.4) in survival, photophysiology (i.e. bleaching, photosynthetic efficiency, and metabolism) and stress defense mechanisms (i.e. heat shock and antioxidant response) of solar-powered sacoglossan sea slugs, from tropical (Elysia crispata) and temperate (Elysia viridis) environments. High temperature was the main factor affecting the survival of both species, while pH only affected the survival of the temperate model. The photobiology of E. viridis remained stable under the combined scenario, while photoinhibition was observed for E. crispata under high temperature and high pCO2. In fact, bleaching was observed within all tropical specimens exposed to warming (but not in the temperate ones), which constitutes the first report where the incidence of bleaching in tropical animals hosting photosynthetic symbionts, other than corals, occurs. Yet, the expulsion of kleptoplasts by the tropical sea slug, allied with metabolic depression, constituted a physiological response that did not imply signs of vulnerability (i.e. mortality) in the host itself. Although the temperate species revealed greater heat shock and antioxidant enzyme response to environmental stress, we argue that the tropical (stenotherm) sea slug species may display a greater scope for acclimatization than the temperate (eurytherm) sea slug. E. crispata may exhibit increased capacity for phenotypic plasticity by increasing fitness in a much narrower thermal niche (minimizing maintenance costs), which ultimately may allow to face severe environmental conditions more effectively than its temperate generalist counterpart (E. viridis).